2017
DOI: 10.1021/acsami.7b02996
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Characterization of ALD-Grown TiO2Protective Layers in Silicon Photocathodes

Abstract: A critical parameter for the implementation of standard high-efficiency photovoltaic absorber materials for photoelectrochemical water splitting is its proper protection from chemical corrosion while remaining transparent and highly conductive. Atomic layer deposited (ALD) TiO layers fulfill material requirements while conformally protecting the underlying photoabsorber. Nanoscale conductivity of ALD TiO protective layers on silicon-based photocathodes has been analyzed, proving that the conduction path is thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 54 publications
4
63
0
Order By: Relevance
“…It has been demonstrated that it can effectively hinder this reaction thanks to the strong proton adsorption on the TiO 2 , which might restrict H 2 formation . However, besides having an effect in this aspect, TiO 2 layers have been used as protective layers of silicon photovoltaics, thanks to its good stability at different pH conditions, especially when it is not polarized at very negative potentials . Interestingly, the obtained results with the photocathode in presence of bismuth evidence that less negative voltages are necessary for performing the electrochemical reaction, so that less harsh conditions are necessary during cycling, assuring better stability for the photoelectrode and the TiO 2 protective layer.…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations
“…It has been demonstrated that it can effectively hinder this reaction thanks to the strong proton adsorption on the TiO 2 , which might restrict H 2 formation . However, besides having an effect in this aspect, TiO 2 layers have been used as protective layers of silicon photovoltaics, thanks to its good stability at different pH conditions, especially when it is not polarized at very negative potentials . Interestingly, the obtained results with the photocathode in presence of bismuth evidence that less negative voltages are necessary for performing the electrochemical reaction, so that less harsh conditions are necessary during cycling, assuring better stability for the photoelectrode and the TiO 2 protective layer.…”
Section: Figurementioning
confidence: 97%
“…Here, we report for the first time on the photoassisted negative half‐reaction (V 3+ /V 2+ ) in presence of bismuth and its role in the electrochemistry of the system, by using a photocathode based on a n + ‐p silicon buried junction (see the Supporting Information for details), protected by a 100 nm TiO 2 layer deposited by atomic layer deposition (TiO 2 /n + ‐p‐Si) . Initially, to analyze the effect of bismuth in the direct‐charge injection, n + degenerated silicon cathodes (TiO 2 /n + ‐Si) were also evaluated in different media.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Being like n‐Si photoanodes, the pn‐Si buried junction and p‐Si based heterojunction were commonly used to construct the photocathodes. The photocathodes with pn + ‐Si buried junction and p‐Si/SiO 2 /Ti MIS heterojunction usually show more positive onset potential (0.5–0.64 V, vs RHE) for water reduction due to its large barrier height. Pt is an active electrocatalyst for hydrogen evolution, but direct deposition of Pt on p‐Si presented a smaller onset potential (0.27 V, vs RHE) .…”
Section: Semiconductors In Photoelectrochemistrymentioning
confidence: 99%